Implementation of Teacher's Pedagogic Competence In The 2013 Curriculum Learning Process in Elementary School - Agustinus Tanggu Daga; Dinn Wahyudin; Rudi Susilana (Green Publisher Indonesia, 2022)
One of the components that support and determine the success of implementing the 2013 curriculum in elementary schools is the role and competence of teachers. The problem that is often encountered in schools is the understanding and awareness of teachers about the role and competence in implementing the 2001 curriculum. This study aims to explain the learning process of the 2013 curriculum in elementary schools, the role of teacher competence in the implementation of learning in elementary schools. This study uses the library method as a research method. Content analysis was used to analyze the research data. The results of this study indicate that (1) the characteristics of the learning process in the 2013 curriculum are integrated thematic learning activities, applying learning steps (introduction, core, closing) according to the 2013 curriculum format, integrating scientific approaches, applying authentic assessment and character education; (2) the role of teacher pedagogic competence in 2013 curriculum learning is to implement integrated thematic learning, apply a scientific approach, utilize media and learning resources, utilize information and communication technology, integrate 21st century skills in the learning process, carry out character education, and carry out authentic assessments.